2014
DOI: 10.1371/journal.ppat.1004290
|View full text |Cite|
|
Sign up to set email alerts
|

A Molecularly Cloned, Live-Attenuated Japanese Encephalitis Vaccine SA14-14-2 Virus: A Conserved Single Amino Acid in the ij Hairpin of the Viral E Glycoprotein Determines Neurovirulence in Mice

Abstract: Japanese encephalitis virus (JEV), a mosquito-borne flavivirus that causes fatal neurological disease in humans, is one of the most important emerging pathogens of public health significance. JEV represents the JE serogroup, which also includes West Nile, Murray Valley encephalitis, and St. Louis encephalitis viruses. Within this serogroup, JEV is a vaccine-preventable pathogen, but the molecular basis of its neurovirulence remains unknown. Here, we constructed an infectious cDNA of the most widely used live-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 112 publications
0
52
0
Order By: Relevance
“…The location of these mutations in all three E protein structural domains and the stem-anchor region indicates that multiple E protein functions, including cell attachment and entry or virus assembly and release, are probably impaired in neurons of the central nervous system. Reversion of individual or combinations of these JEV SA14-14-2 E protein mutations to the WT amino acid (such as F107L, K138E, G244E, and possibly V315A) is capable of restoring some level of neurovirulence in mice (27)(28)(29), emphasizing that their cumulative effect on neurovirulence attenuation is critical for vaccine safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location of these mutations in all three E protein structural domains and the stem-anchor region indicates that multiple E protein functions, including cell attachment and entry or virus assembly and release, are probably impaired in neurons of the central nervous system. Reversion of individual or combinations of these JEV SA14-14-2 E protein mutations to the WT amino acid (such as F107L, K138E, G244E, and possibly V315A) is capable of restoring some level of neurovirulence in mice (27)(28)(29), emphasizing that their cumulative effect on neurovirulence attenuation is critical for vaccine safety.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies support this conclusion and have demonstrated that passage of JEV SA14-14-2 in mouse brain results in amino acid substitutions in the E protein that produce a neurovirulent phenotype (27,28). However, a recombinant WT JEV Nakayama clone containing prM-E or 5=-UTR-C-prM-E of the JEV SA14-14-2 vaccine strain produced viruses with similar or moderately lower levels of neurovirulence than that of the WT parent virus (29), suggesting that mutations in other regions of the virus genome also contribute to attenuation.…”
mentioning
confidence: 80%
“…We used one-day-old neonatal mice, as this stage of development is analogous to the second trimester of pregnancy in humans. Upon intracerebral injection (18,19), all three contemporary strains led to 100% mortality in neonatal mice, with typical neurological manifestations such as inactivity, motor weakness, and bilateral hind limb paralysis. By contrast, CAM/2010 killed only 16.7% animals (Fig.…”
mentioning
confidence: 99%
“…There again, the molecular basis of JEV-SA 14 -14-2 attenuation is unclear. Two mutations in the E protein were found as important factors: the mutation E138K was involved in viral clearance (81) and interferon antagonism (46), while the mutation E244G was recently linked to neurovirulence attenuation (82). Additionally JEV-SA 14 -14-2 did not appear to produce the NS1= protein (83), an important factor in viral neuroinvasiveness (84).…”
Section: Discussionmentioning
confidence: 99%